Agricultural structure management based on water–energy–food and carbon sink scenarios in typical fuel ethanol raw material planting areas—a case study of the Hulan River Basin, Northeast China - Cui, Guannan; Wang, Haitao; Li, Xiaofei; Li, Wenchao; Li, Huijie; Dong, Liming (Frontiers in Environmental Science, 2025)
The implementation of Chinese policies promoting fuel ethanol has significantly influenced the land use structure, water resources, and soil environment in ethanol raw material planting areas. This paper focuses on the Hulan River Basin, a benchmark region for maize cultivation, to investigate the specific crop allocation issues in relation to the impact of land use changes on water quality. The study projects an environmentally and economically sustainable structure for the cultivation of fuel ethanol raw materials using the CLUE-S model and multiple linear programming. Additionally, the carbon sequestration potential is assessed under different scenarios. Throughout the study period, the net ecosystem productivity (NEP) in the Hulan River Basin demonstrated variability, evidenced by a decrease of 33.96 gC·m−2·a−1 from 2010 to 2015 and a subsequent augmentation of 55.64 gC·m−2·a−1 from 2015 to 2020. Furthermore, the three scenarios (Grain Crop Priority Policy, Fuel Ethanol Crop Priority Policy, and Carbon Storage Priority Policy) effectively addressed the requirements for land use/cover types and enhanced carbon sequestration within the study area. Consequently, the outcomes provide a conceptual foundation for regional policymakers, providing insights into the refinement of land use within ethanol crop zones and fostering the advancement of the fuel ethanol industry, thus undergirding prospective land use strategies and refinement from the water, energy, food, and carbon perspectives.